Raw material variability as archaeological tools: Preliminary results from a geochemical study of the basalt vessel workshop at Iron Age Tel Hazor, Israel - Gluhak, Tatjana; Rosenberg, Danny; Ebeling, Jennie (Journal of Lithic Studies, 2016)
The discovery of a basalt vessel workshop at Tel Hazor, one of the most important Iron Age sites in the Near East, marks a turning point in our understanding of stone artifact production and distribution during the1st millennium BCE. It offers a rare opportunity to characterize ancient raw material sources, production sites, and study production, trade and distribution systems. The basalt vessel workshop, the only one of its kind in the Levant, produced large quantities of bowl preforms and production waste. To better understand the production and distribution systems behind this specialized production center, in 2011 we initiated a focused geochemical project that concentrated on the products of this unique workshop. We measured the major and trace element composition of 44 unfinished basalt vessels from the workshop and other contexts at Hazor, and can demonstrate that the majority of these objects were derived from one specific, geochemically well-constrained, basaltic rock source. Only a few bowls clearly deviate from this geochemical composition and were produced using raw material from other sources. Thus, we believe that one major quarry existed that supplied the Hazor workshop with the majority of the basaltic raw material. The products from this specific extraction site provide us with a “Hazor reference group” that can be used to test whether or not finished vessels from Hazor and contemporary sites were produced in the Hazor workshop.